Nutraceutical fatty acids from oleaginous microalgae : a human health perspective - Patel, Alok Kumar; Matsakas, Leonidas (John Wiley & Sons, Inc., 2020)
"As new diseases, climate change, environmental disasters, economic and other hardships affect various parts of the globe or the entire Earth's population itself, it is increasingly more important to understand human health, nutrition, and where those two intersect in the field of engineering and food science. Books like this one further the scientific and engineering communities' discussions and research in these areas"--